Characterization of two coleopteran α-amylases and molecular insights into their differential inhibition by synthetic α-amylase inhibitor, acarbose. (July 2016) - Channale, Sonal M.; Bhide, Amey J.; Yadav, Yashpal; Kashyap, Garima; Pawar, Pankaj K.; Maheshwari, V.L.; Ramasamy, Sureshkumar; Giri, Ashok P.
Abstract: Post-harvest insect infestation of stored grains makes them unfit for human consumption and leads to severe economic loss. Here, we report functional and structural characterization of two coleopteran α-amylases viz . Callosobruchus chinensis α-amylase (CcAmy) and Tribolium castaneum α-amylase (TcAmy) along with their interactions with proteinaceous and non-proteinaceous α-amylase inhibitors. Secondary structural alignment of CcAmy and TcAmy with other coleopteran α-amylases revealed conserved motifs, active sites, di-sulfide bonds and two point mutations at spatially conserved substrate or inhibitor-binding sites. Homology modeling and molecular docking showed structural differences between these two enzymes. Both the enzymes had similar optimum pH values but differed in their optimum temperature. Overall, pattern of enzyme stabilities were similar under various temperature and pH conditions. Further, CcAmy and TcAmy differed in their substrate affinity and catalytic efficiency towards starch and amylopectin. HPLC analysis detected common amylolytic products like maltose and malto-triose while glucose and malto-tetrose were unique in CcAmy and TcAmy catalyzed reactions respectively. At very low concentrations, wheat α-amylase inhibitor was found to be superior over the acarbose as far as complete inhibition of amylolytic activities of CcAmy and TcAmy was concerned. Mechanism underlying differential amylolytic reaction inhibition by acarbose was discussed. Graphical abstract: Highlights: Callosobruchus chinensis and Tribolium castaneum α-amylases differed in their biochemical properties. CcAmy and TcAmy showed differential inhibition pattern towards synthetic inhibitor, acarbose. Mechanism underlying differential mode of inhibition was studied using molecular docking studies. Two mutations around binding site in T . castaneum α-amylase were responsible for narrow entry point for acarbose.